2000
DOI: 10.1128/jvi.74.6.2888-2894.2000
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adeno-Associated Virus Expressing Human Papillomavirus Type 16 E7 Peptide DNA Fused with Heat Shock Protein DNA as a Potential Vaccine for Cervical Cancer

Abstract: In this study, we explore a potential vaccine for human papillomavirus (HPV)-induced tumors, using heat shock protein as an adjuvant, a peptide vaccine for safety, and adeno-associated virus ( Cervical carcinoma remains one of the most common malignancies worldwide, with 500,000 new cases diagnosed each year (5) and 200,000 cervical cancer deaths annually (21). Human papillomavirus type 16 (HPV-16) is the predominant etiologic agent of cervical cancer and carries three transforming oncogenes, E5, E6, and E7 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 42 publications
2
94
0
Order By: Relevance
“…However, in a majority of such literature, AAV2-delivered transgenes that have been reported tobe capable of inducing immune responses that are either pathogen-specific antigens when AAV2 vectors were specifically designed as vaccine, [38][39][40] or highly pathogenic in nature (eg ovalbumin, b-Gal). In contrast, the transgenes used in our study (eg GFP) have not been shown to elicit antibody responses when delivered by AAV into immunocompetent animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a majority of such literature, AAV2-delivered transgenes that have been reported tobe capable of inducing immune responses that are either pathogen-specific antigens when AAV2 vectors were specifically designed as vaccine, [38][39][40] or highly pathogenic in nature (eg ovalbumin, b-Gal). In contrast, the transgenes used in our study (eg GFP) have not been shown to elicit antibody responses when delivered by AAV into immunocompetent animals.…”
Section: Discussionmentioning
confidence: 99%
“…HSPs have been used to enhance the potency of DNA vaccines by others, 46,47,49,50 but there are several important differences between their strategy and ours. The E7/ HSP70 fusion protein in the present report is designed to be secreted by transfected cells and targeted to DCs, as compared to cytoplasmic expression of transfected cells in previous systems.…”
Section: Hsp70-mediated Antigen Targeting For Dna Vaccines H Hauser Ementioning
confidence: 99%
“…Several approaches have been described for the induction of HPV-specific CTL responses such as immunization with recombinant viruses, HPV-specific proteins or peptides, E7 linked to heat shock proteins or intracellular sorting molecules, peptides/proteins loaded on dendritic cells, DNA-or RNA-transfected dendritic cells (DCs) or cell lines. [8][9][10][11][12][13] We are exploiting the Semliki Forest virus (SFV) expression system. 5,[14][15][16][17] This vector represents an ideal system for the induction of cellular immune responses against the oncoproteins HPV E6 and E7 since, apart from its high efficiency and biosafety, SFV RNA does not integrate and SFV infection is cytolytic by apoptosis.…”
Section: Introductionmentioning
confidence: 99%